Edukasi dan Pembinaan Kader Dalam Peningkatan Pengetahuan Dalam Penilaian Pertumbuhan dan Perkembangan Balita di Posyandu - Gusti Lestari Handayani; Vivianti Dewi (Indonesia Berdaya, 2023)
Early detection of developmental abnormalities in infants reduces the risk of more serious illnesses. The purpose of the activity is to carry out Community Service Activities through educational activities and increase the ability of cadres in assessing growth and development as well as stimulation for toddlers at the Posyandu in the working area of the Aurduri Health Center, Jambi City, namely to increase cadre knowledge about procedures for assessing growth and development of toddlers, to be able to provide proper consultation for mothers of toddlers related to the results of the assessment of growth and development, as well as its stimulation. This community service method is carried out by providing education in the form of counseling, conducting demonstrations in assessing the growth and development of toddlers and their stimulation. and to evaluate it is done by using a pretest and post test questionnaire to assess the mother's knowledge and observation to assess the skills of cadres. The results of the implementation of the activities obtained an increase in the knowledge and skills of cadres regarding the assessment of growth and development of toddlers and their stimulation. The implementation of service activities is further enhanced in an effort to increase the knowledge and skills of cadres not only in assessing growth but also in the development of toddlers.